Інтеграція сучасних технологій менеджменту в практику управління персоналом: вплив на ефективність використання робочого часу - Крайнік, О.М. (Економічний вісник Донбасу, 2025)
У статті розглядається інтеграція сучасних технологій менеджменту в систему управління персоналом та їх вплив на ефективність використання робочого часу. Визначено, що цифрові інструменти, автоматизація бізнес-процесів, аналітика даних і технології тайм-менеджменту сприяють оптимізації організаційних процесів, підвищенню продуктивності та зменшенню втрат часу. Обґрунтовано значення застосування інноваційних підходів для раціонального розподілу трудових ресурсів і формування гнучкої системи управління. Зроблено висновок, що використання сучасних управлінських технологій є ключовим чинником підвищення ефективності роботи персоналу та конкурентоспроможності організації. The article examines the integration of modern management technologies into human resource management and their impact on the efficiency of working time utilization. In the era of digital transformation, the adoption of innovative tools becomes a key factor in strengthening organizational competitiveness and improving employee productivity. The study highlights the role of digital platforms, HR process automation, data analytics, and time management systems as essential components that optimize workflows and ensure the rational distribution of time. Special attention is given to the potential of technological solutions in reducing time losses from routine administrative tasks, enhancing communication, and supporting decision-making. The implementation of automated planning systems, cloud-based HR services, and employee monitoring tools enables managers to allocate tasks more effectively, set priorities, and boost employee engagement. Moreover, integrating modern time management practices into HRM contributes to work-life balance, which positively affects motivation and labor efficiency. It is also emphasized that the integration of advanced technologies requires new competencies from HR specialists, including digital literacy, analytical thinking, and adaptability. Combining human resource potential with technological capabilities creates opportunities to minimize unproductive time, ensure flexibility, and foster a culture of continuous improvement. The research concludes that systematic application of modern management technologies in HR practices acts as a driver for enhancing working time efficiency, supporting organizational sustainability, and building long-term competitive advantages.